2008
DOI: 10.1002/cb.262
|View full text |Cite
|
Sign up to set email alerts
|

Who are ethnocentric? Examining consumer ethnocentrism in Chinese societies

Abstract: This study examined consumer ethnocentrism in Chinese societies and further to reveal whether more ethnocentric consumers would have higher preferences of domestic products. Multi-item CETSCALE was applied in the study. Consumer surveys were administered in Taipei, Taiwan and in Shanghai, China, using stratified sampling method following the age and gender distributions of the populations between the ages of 15 and 64 in Taipei and in Shanghai. The differences in consumer ethnocentrism from respondents in Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 15 publications
10
75
0
2
Order By: Relevance
“…The attitude above is conforming to the term of nationalism attitude that stated by some researchers, such as, Cleveland et al (2009), John and Bradly (2009), and Hsu and Nien (2008 who pointed out that consumers prefer domestic products rather than foreign products.…”
Section: Nationalismsupporting
confidence: 70%
See 3 more Smart Citations
“…The attitude above is conforming to the term of nationalism attitude that stated by some researchers, such as, Cleveland et al (2009), John and Bradly (2009), and Hsu and Nien (2008 who pointed out that consumers prefer domestic products rather than foreign products.…”
Section: Nationalismsupporting
confidence: 70%
“…Thus becomes an interesting variable in consumer behavior since it is adopted from the field of sociology. There are many studies that investigate the role of ethnocentrism in the context of consumer behavior, including Cleveland et al (2009), John and Brady (2009), Horn (2009), Nien Hsu (2008), and Sihombing (2005. Cleveland et al (2009) revealed that the Consumer Ethnocentrism Tendency (CET) and materialism (MAT) are very suitable for predicting the behavior of a consumer.…”
Section: Ethnocentrismmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that socio-psychological factors including patriotism and nationalism (Vida & Fairhurst, 1999;Yelkur, Chakrabarty & Bandyopadhyay, 2006;Javalgi et al, 2005) influence consumers' ethnocentric dispositions considerably. With respect to age, it has been shown that while older shoppers are more hardened in their brand loyalty and consequently more difficult to switch to other brands, including foreign brands (Auty & Elliot, 1998), younger consumers show a stronger inclination to buy foreign products (Sharma, Shimp & Shin, 1995;O'Cass & Lim, 2002;Wang, Siu, & Hui, 2004;Hsu & Nien, 2008). Levels of education also impact attitudes to foreign goods.…”
Section: Demographic Characteristics Ethnocentrism and Brand Perceptionmentioning
confidence: 99%